Vertical profiles of HCN, HC3N, and C2H2 in Titan's atmosphere derived from Cassini/CIRS data - Teanby, N; Irwin, P; de Kok, R; Vinatier, S; Bezard, B; Nixon, C; Flasar, F; Calcutt, S; Bowles, N; Fletcher, L; Howett, C; Taylor, F (2007)
Mid-infrared limb spectra in the range 600-1400 cm-1 taken with the Composite InfraRed Spectrometer (CIRS) on-board the Cassini spacecraft were used to determine vertical profiles of HCN, HC3N, C2H2, and temperature in Titan's atmosphere. Both high (0.5 cm-1) and low (13.5 cm-1) spectral resolution data were used. The 0.5 cm-1 data gave profiles at four latitudes and the 13.5 cm-1 data gave almost complete latitudinal coverage of the atmosphere. Both datasets were found to be consistent with each other. High temperatures in the upper stratosphere and mesosphere were observed at Titan's northern winter pole and were attributed to adiabatic heating in the subsiding branch of a meridional circulation cell. On the other hand, the lower stratosphere was much colder in the north than at the equator, which can be explained by the lack of solar radiation and increased IR emission from volatile enriched air. HC3N had a vertical profile consistent with previous ground based observations at southern and equatorial latitudes, but was massively enriched near the north pole. This can also be explained in terms of subsidence at the winter pole. A boundary observed at 60° N between enriched and un-enriched air is consistent with a confining polar vortex at 60° N and HC3N's short lifetime. In the far north, layers were observed in the HC3N profile that were reminiscent of haze layers observed by Cassini's imaging cameras. HCN was also enriched over the north pole, which gives further evidence for subsidence. However, the atmospheric cross section obtained from 13.5 cm-1 data indicated a HCN enriched layer at 200-250 km, extending into the southern hemisphere. This could be interpreted as advection of polar enriched air towards the south by a meridional circulation cell. This is observed for HCN but not for HC3N due to HCN's longer photochemical lifetime. C2H2 appears to have a uniform abundance with altitude and is not significantly enriched in the north. This is consistent with observations from previous CIRS analysis that show increased abundances of nitriles and hydrocarbons but not C2H2 towards the north pole. © 2006 Elsevier Inc. All rights reserved.